2017
DOI: 10.1101/137307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA damage checkpoint dynamics drive cell cycle phase transitions

Abstract: DNA damage checkpoints are cellular mechanisms that protect the integrity of the genome during cell cycle progression. In response to genotoxic stress, these checkpoints halt cell cycle progression until the damage is repaired, allowing cells enough time to recover from damage before resuming normal proliferation. Here, we investigate the temporal dynamics of DNA damage checkpoints in individual proliferating cells by observing cell cycle phase transitions following acute DNA damage. We find that in gap phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…There are two key events that punctuate the cell cycle progression: DNA replication, when nuclear genome is duplicated - which defines S (synthesis) phase -, and mitosis (M phase), defined as the period in which chromosomes are condensed, sorted and then equally distributed to daughter cell ( Hustedt and Durocher, 2017 ). During DNA replication, genotoxic stresses (such as DNA damage and incomplete replication) activate the checkpoints pathways, which prevents cell cycle progression until the damage are repair ( Chao et al., 2017 ). These checkpoints have the role of checking if the replication have been properly accomplished, and there are no physical impediments for chromosomes to be replicated or repaired prior to nuclear division ( Hartwell and Weinert, 1989 ; Russell, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are two key events that punctuate the cell cycle progression: DNA replication, when nuclear genome is duplicated - which defines S (synthesis) phase -, and mitosis (M phase), defined as the period in which chromosomes are condensed, sorted and then equally distributed to daughter cell ( Hustedt and Durocher, 2017 ). During DNA replication, genotoxic stresses (such as DNA damage and incomplete replication) activate the checkpoints pathways, which prevents cell cycle progression until the damage are repair ( Chao et al., 2017 ). These checkpoints have the role of checking if the replication have been properly accomplished, and there are no physical impediments for chromosomes to be replicated or repaired prior to nuclear division ( Hartwell and Weinert, 1989 ; Russell, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although not explored in this study, the increased variability upon BRCA1 or BRCA2 knockdown may result from the cell cycle dependence of homologous recombination, which occurs only in S and G2 phase after replication of DNA. Singlecell studies of cell cycle regulation in response to DSBs have shown that the timing of DNA damage has pronounced effects on cell fate determination (Chao et al, 2017). As such, cells in different cell cycle phases may generate distinct p53 dynamics in response to the same genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigated if uncontrolled E2F-dependent transcription during S phase also results in an altered response to exogenous DNA damage. We treated cells with the radiomimetic drug neocarzinostatin (NCS), which causes double-stranded DNA breaks (DSBs) irrespective of cell-cycle phase (Chao et al, 2017). Furthermore, NCS is highly unstable, which allows cells to recover without the need to wash the drug away during live-cell imaging experiments.…”
Section: Deregulated E2f-dependent Transcription During S/g2mentioning
confidence: 99%